Value Relevance of Earnings and Book Value of Equity: Evidence from Malaysia (Global Business Management Review (GBMR), 2020)
The purpose of this paper is to examine the value relevance of accounting information in the Malaysian main capital markets’ firms by employing the basic Ohlson model. The study employs Prais-Winsten regression, correlated panels corrected standard errors (PCSEs) to analyze data due to the existence of cross sectional dependence across panels. The results show that the book value of equity is significantly value relevant variable in decision making, while earnings are not as opposed to the conceptual framework for financial reporting. It shows that investors focus on the book value of equity while less emphasis on earnings in investment decision making due to the perception of managerial bias in the reported earnings.